Development of decision making for punishment module on college web portal / Noraishah Rahimah Omar - Omar, Noraishah Rahimah (2006)
This thesis has discussed the concept of decision support system in organization that are interactive, flexible, and adaptable computer-based information system. Usually from the scenarios at Teratai College making decision to punish students it takes times to produce the desired result. One of the major problems was to get the correct information with those processes of making decision in order to have a result. It was difficult to make the decision based on the subjects that have been done if there is no guideline to be followed. These problems may lead to the ineffectiveness result of action that should be produced. Therefore with this study attempt to find a solution how a portal may help to assist the staff in getting the decision. The project objective is to develop a web based DSS to the staff of Teratai College. The decision making process in this module using forward chaining methods. It based on the rules to achieve the goals. The goals are to produce a compound and suggestion to the decision. Decision support system appear well suited to problems of this nature as it can help facilitate problem solving flows and aid decision maker in addressing unstructured or semi-structured decision. DSS combined the intellectual resources of individuals with the capabilities of the computer to improve the quality of decisions. Thus the decision support system is a useful tools selection for principle and resident staff at Teratai College to make decision.